Effects of lumbar myelography on subarachnoid pressure and cardiorespiratory parameters in healthy sheep - Minto, Bruno W. [UNESP] (2021)
The purpose of this study was to evaluate the effects of lumbar myelography on subarachnoid pressure, cardiorespiratory parameters and pressure-volume index in sheep. Eight sheep were evaluated. The animals were submitted to puncture of the cisterna magna for monitoring of subarachnoid pressure (SaP). Lumbar myelography was performed through applying Iohexol (0.4mL/kg). ToC, PAS, PAD, MAP, InspISO, FeISO, SaP and CPP were recorded immediately after anesthetic stabilization (M0), during lumbar puncture (M1), and two, four and six minutes after contrast application (M2, M3 and M4, respectively). Blood pressure initially increased, then decreased, returning to basal level, similarly observed for InspISo and FeISo. The SaP rose initially thereafter remaining stable. Despite of the effect on subarachnoid pressure, lumbar myelography can be considered safe in sheep.